Assessment in Game-Based Learning
XXVIII, 464 p.
Keywords: The capabilities and possibilities of emerging game-based learning technologies bring about a new perspective of learning and instruction. This, in turn, necessitates alternative ways to assess the kinds of learning taking place in the virtual worlds or informal settings. Aligning learning and assessment is at the core of creating a favorable and effective learning environment, one that is learner-centered, knowledge-centered, and assessment-centered. However, how do we know students have learned in games? What do we assess, and how do we assess students’ learning outcomes in a game-based learning environment? After a critical literature review, the authors discovered that there is a missing link between game-based learning and game-based assessment, particularly in assessing complex problem solving processes and outcomes in a digital game-based learning environment. This edited volume bridges the gap by providing that missing link. It covers the current state of research, methodology, assessment, and technology of game-based learning. The contributions from international distinguished researchers present innovative work in the areas of educational psychology, educational diagnostics, educational technology, and learning sciences. Included chapters are organized into three major parts: (1) Foundations of game-based assessment, (2) technological and methodological innovations for assessing game-based learning, and (3) realizing assessment in game-based learning. It provides theoretical research, translational resaerch, and guided practice---all in one volume. This book will prove invaluable to anyone who is performing research or working the the field--it provides a springboard from theory to practice, offering a map for anyone hoping to implement game-based assessment into their institution as well as to primary researchers and developers.